A Novel Smartphone-Based Color Test for Detection of Color Vision Defects in Age Related Macular Degeneration. (31st March 2022) - Karampatakis, Vassilios; Almaliotis, Diamantis; Karamitopoulos, Leonidas; Kalliris, George; Almpanidou, Stavroula
Abstract : Purpose . To evaluate the efficacy of the smartphone-based K -color test to detect color defects in patients with Age-related Macular Degeneration (AMD). Methods . 88 patients ( n  = 135 eyes) with AMD and 28 controls ( n  = 53 eyes) underwent color testing with the Hardy–Rand–Rittler (H-R-R), the K -color test, and the Ishihara test. The K -color test presents randomized colored shapes in decreasing steps of intensity, providing also a record system for result tele-transmission. Sensitivity, specificity, and reliability were examined to investigate the validity of the novel test. 26 participants with AMD also completed a questionnaire regarding the feasibility of the test. Results . Linear mixed-effects models indicated a significant difference (p < 0.001 ) between AMD and normal eyes. The areas under the curve (AUC) were estimated to be 0.897 [95% CI: 0.841–0.952], 0.943 [95% CI: 0.901–0.984], and 0.931 [95% CI: 0.886–0.977] for the red, green, and blue color, respectively. Based on the H-R-R, the sensitivity of the test was 0.79, 0.90, and 0.95 for the red, green, and blue colors, respectively, and specificity was 0.88 for all colors. The new test recognized more abnormal cases than the Ishihara (sensitivity of 0.98 and 1.0 and specificity of 0.48 and 0.38 for red and green colors, respectively). Test-retest reliability was found to be high for the red [ICC = 0.996 (0.990–0.999)], green [ICC = 0.974 (0.929–0.990)], and blue [ICC = 0.992 (0.981–0.997)] colors. The majority of the asked participants stated that they could easily perform the test. Conclusion . The K -color test was found to be sensitive and specific in detecting color defects in AMD patients. The K -color test may serve as a useful tool both for patients and their physicians.